Perancangan Sistem Informasi Manajemen Bimbingan Belajar dengan menggunakan Google Calendar API Studi Kasus: Lembaga Bimbingan Belajar Omega - Bella Vian Oktavia; Widhy Hayuhardhika Nugraha Putra; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Omega is a tutoring institution located in Cilegon City, Banten Province, and was established to provide non-formal learning assistance and guidance to students from elementary, junior high, and high school levels to improve achievement or study optimally. In carrying out its business processes, teacher and student identity data collection, scheduling, and payment at Omega are still made manually. Teacher and student identity data collection is carried out through administrative staff writing them in the notebooks provided. Regarding the scheduling process, the administrative staff informs each individual or group of students via the Whatsapp chat messenger. As for payments, Omega only accepts cash payments and does not accept bank transfers. Payment recording is still done manually. Based on these problems, it is necessary to analyze the system requirement and document the Omega Tuition Management Information System design, which can provide an overview of what kind of system will be made before entering the implementation stage. The system is designed based on a website and integrated with Google Calendar API to manage scheduling functions and Midtrans Payment Gateway to manage payment functionalities. This research resulted in 18 use cases, 18 activity diagrams, 18 sequence diagrams, and 18 UI designs. Tests are carried out using the Traceability Matrix to test the design documents made and Prototype Testing to test the prototypes made. In testing the Traceability Matrix, the results show that all the requirements and design documents are according, and prototype testing obtains "Valid" results for the entire test scenario.